Development of Indonesian Original Medicines Study of Standardized Herbal Medicine Products "Tolak Angin" as Traditional Medicine - Nastiti, Kunti; Maharani, Tri Anita; Trisia, Trisia; Kristiani, Windilla; Khadijah, Siti (PROMOTOR, 2024)
The use of traditional medicine continues to grow rapidly in Indonesia, reflecting the country's abundant natural and cultural wealth. One of the leading herbal medicine products is Tolak Angin, which is produced by PT. Sidomuncul Herbal and Pharmaceutical Industry, Tbk. Tolak Angin is a Standardized Herbal Medicine (OHT) that has been scientifically tested for its safety, quality, and benefits. This article presents an overview of the ingredients, production process, and clinical trials of Tolak Angin, as well as its impact in the context of Indonesian public health. By involving literature studies and secondary data analysis, this article highlights the importance of standardization in the development of effective and safe traditional medicine products. In conclusion, Tolak Angin not only represents local cultural heritage and knowledge, but also plays a vital role in providing affordable and reliable treatment alternatives for the community.